Redefining Assistive Technology: A Shift from Disability to Functional Impairments in Policy and Practice - Goyal, Ishita; Rana, Salaj; Rani, Geeta; Senjam, Suraj Singh; Singh, Ravinder (Indian Journal of Community Health, 2025)
Achieving the Sustainable Development Goals (SDG) and ensuring inclusive universal health coverage (UHC) with the goal of “leaving no one behind” has sparked a global dialogue on Assistive Technology (AT) or Assistive Products (AP).(1) This conversation has driven innovation and transformed lives, yet the unmet needs for AT are significant globally. The WHO-UNICEF Global Report on Assistive Technology (GReAT) 2022 reported that in low- and middle-income countries (LIMCS), as low as 3% of the population needing AT has access to these life-changing tools.(2) Further, it is estimated that by 2050, two billion people will require AT, yet 90% of them, particularly in LMICs, will lack access.(3) The International Organization for Standardization (ISO) has defined “assistive product as any product (including devices, equipment, instruments, and software), specially produced or generally available, used by or for persons with disability for participation; to protect, support, train, measure or substitute for body functions/structures and activities; or to prevent impairments, activity limitations or participation restrictions.(4) For ease of understanding, the authors use AT as the umbrella term in the rest of the article for Assistive technology or aids or products or services.